PERAN KELOMPOK KEAGAMAAN DALAM PEMILIHAN KEPALA DESA DI DESA GUBUG KECAMATAN GUBUG KABUPATEN GROBOGAN TAHUN 2013 - Gagas Tutur Pamungkas; Susilo Utomo; Mohammad Adnan (Journal of Politic and Government Studies, 2014)
AbstractThe election of the village is a from of democracy party perfomed within the scope of the village. Leadrs directly elected by the public, so public can determine by choice in accordance with conscience them.The research was conducted using qualitative method with descriptive approach with the enrichment of material throught the study of librarianship (documentation) and in-depth interviews conducted with a range of informan-related in the field. Informant this research consisted of village chief candidates, religious figures from Muhammadiyah and Nahdlatul Ulama and other informant with the theme of research. The results of research shows, that in the election of the village chief ( pilkades ) in the village of gubug behavior choose masyrakat much influenced by the role of religious groups that compete to compete for the seat of the highest in the village of gubug.Religious groups that compete is of muhammadiyah and nahdlatul ulama.Many ways done from each side to get support from masyrakat, of muhammadiyah do start of the campaign, organize match futsal, the absorption of the aspirations of residents, until political money. So also from nahdlatul ulama negotiate with people by means of religious meeting until political money.In the end the election was won by a candidate from religious groups nahdlatul ulama who have less capital social as well as lacking in capital and financial.With these roles religious group nahdlatul ulama that has power patron-klien is strong.